SOSIALISASI DESAIN KONTEN GAMBAR SEBAGAI DIGITAL MARKETING DI MEDIA SOSIAL MENGGUNAKAN APLIKASI CANVA BAGI UMKM DI DESA SELEBUNG KABUPATEN LOMBOK TENGAH - I Gusti Agung Didit Eka Permadi; Asri Oktiani; Faezal Faezal (LPPM Institut Pendidikan Nusantara Global, 2025)
Digital marketing is a marketing activity that utilizes digital technology to facilitate interactions between producers, intermediaries, and potential consumers. Selebung Village is located in Batukliang District, Central Lombok Regency, West Nusa Tenggara (NTB) Province. MSMEs in Selebung Village consists of from business handycrafts/art shop, various snacks fried food sasak, shop/outlet fruits, coffee shops, and others. However, MSME actors in the village this part big not yet do social media promotion. In the ever evolving digital era, digital marketing has become a key element of modern business strategy. The use of online graphic design tools like Canva has made it easier for businesses, marketers, and individuals to create engaging and captivating visual content. The methods used in this community service activity were mapping, design, and outreach and mentoring. The activity began with a focus group discussion with representatives of MSMEs in Selebung Village to determine the extent of understanding regarding the importance of engaging image content on social media and the Canva application. The results of the discussion indicated that many did not yet understand the importance of engaging content and the use of the Canva application. The activity continued with a presentation on the Canva application. The conclusions obtained were through the use of the Canva app, it is hoped that in the future, MSMEs in Selebung Village will increase their creativity and become more skilled at creating image and other content. The recommendation is that MSMEs in Selebung Village be encouraged to create engaging promotional media, such as image content designs for social media and brochures, to increase their business competitiveness and branding, which will ultimately lead to increased sales.